Preterm Small Gestational Age Newborns: Impact on Renal Size and Function - El-Sharkawy, Marwa; Badawy, Magda; Abd El Dayem, Soha M.; Badr, Ahmed; Salama, Hassan; Abdou El-Sherbini, Inji Galal El-Dine; El-Momeim, Sherif Abd (Open Access Macedonian Journal of Medical Sciences, 2020)
OBJECTIVE: The objective of the study was to evaluate the size and function of the kidney in high-risk premature small gestational age (PT/SGA) newborns. Furthermore, estimation of the glomerular filtration rate (GFR) was done by comparing Cystatin C-based method with the creatinine –based method in those preterm newborns. PATIENTS AND METHODS: The study included 20 PT/SGA and controls (20 preterm appropriate for gestational age [PT/AGA] and 20 full-term [FT] newborns). Serum creatinine, blood urea nitrogen, and cystatin C were determined on days 3 and 7 of the study for all newborn infants. GFR was assessed by cystatin C-based method and creatinine-based method. Evaluation of the renal size by ultrasound was done on day 7 of neonatal life. RESULTS: A significant difference was found in the length and transverse diameter of both kidneys, comparing PT/SGA group with PT/AGA and FT group. Cystatin C on day 3 of PT/SGA group had a significant difference than PT/AGA and FT group. Estimation of GFR (eGFR) calculated by filler Zappitelli, Grubb, Larsson, and Dorum formulae of PT/SGA group had a significant difference comparing with PT/AGA and FT group on days 3 and 7. CONCLUSION: PT/SGA newborns have reduced renal size and immature renal function. Cystatin C is a marker for renal function superior to creatinine as it is not affected by body mass index, gestational age, and birth weight. Cystatin C-based eGFR is more accurate and more sensitive to minor changes in GFR than creatinine-based equation.